Développement de la posture intellectuelle d'étudiants universitaires dans un programme innovant - Christelle Lison; Denis Bédard
This article aims to present some of the results of an appreciative inquiry whose overall purpose is to validate the predictors of students' engagement and perseverance in an innovative undergraduate medical programme at the University of Sherbrooke (Canada). The article explores the development of their intellectual posture according to Perry's approach (1970, 1981). To do this, data were collected through a questionnaire addressed to 288 students and with a group of 12 students who took part in a focus group. The results show that the students adopt a relativistic profile, and this regardless of the number of years of training and gender. This leads to believe that the students selected by the programme present a higher relativistic profile at the start of the course, which is then reinforced by the programme.